Integration of Islamic Principles and Modern Educational Theories in Islamic Education - Hadi, Abdul; Anim, Sarbini; Yasin, Hadi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research explores the integration of Islamic principles with modern educational theories to develop an understanding of Islamic education as a transformative platform to achieve human perfection. Based on the principles of Maqasid al-Sharia, which includes basic human rights such as Faith, Life, Intelligence, Heredity, and Wealth, Islamic education focuses on a holistic approach that includes spiritual, moral, and intellectual dimensions. The method used in this study is qualitative, with literature review as the main approach to analyzing diverse sources from Islamic teachings, Muslim philosophers, and Western thinkers. This research identifies trends and commonalities of concepts related to human development and perfection through different philosophical and religious perspectives. The study results show that Islamic education not only aims to provide knowledge but also to encourage spiritual, moral, and intellectual development that is in harmony with the universal principles of human dignity and perfection. The conclusion of this study suggests that Islamic education with a holistic approach can empower individuals to contribute meaningfully to society while achieving personal fulfillment. The implications of this research can enrich educational practices by integrating Islamic values into human development toward perfection, both at the individual and community levels.